2016
DOI: 10.1007/s40620-016-0351-0
|View full text |Cite
|
Sign up to set email alerts
|

The duration of acute kidney injury after cardiac surgery increases the risk of long-term chronic kidney disease

Abstract: Patients developing AKI after cardiac surgery presented high prevalence of long-term incident CKD. The duration of AKI was a strong independent risk factor for this late CKD development. Recognition of predictive factors for CKD development following cardiac surgery-associated AKI may help to develop strategies to prevent or halt CKD progression in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 23 publications
3
46
1
Order By: Relevance
“…Our results showed that the risk of CKD increased with the severity of CSA-AKI regardless if renal function was restored at discharge, which was in accordance with the findings of previous studies [7,17]. Notably, the cumulative incidence of CKD stages 3-5 was relatively low (9.9%) in the AKI group, as compared to other studies [7,16], which may be explained by the relatively younger age and lower rate (4.8%) of aortic surgery, which had a great impact on the progression of kidney function [18]. In addition, the signs of CKD may not be detected by routine methods, such as eGFR, proteinuria, and blood pressure measurements [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that the risk of CKD increased with the severity of CSA-AKI regardless if renal function was restored at discharge, which was in accordance with the findings of previous studies [7,17]. Notably, the cumulative incidence of CKD stages 3-5 was relatively low (9.9%) in the AKI group, as compared to other studies [7,16], which may be explained by the relatively younger age and lower rate (4.8%) of aortic surgery, which had a great impact on the progression of kidney function [18]. In addition, the signs of CKD may not be detected by routine methods, such as eGFR, proteinuria, and blood pressure measurements [19].…”
Section: Discussionsupporting
confidence: 92%
“…Palomba et al [16] reported that the 12-month prevalence of CKD was 9% in the non-AKI patients versus 25% in the AKI group in a total 350 of patients who underwent elective cardiac surgery. Our results showed that the risk of CKD increased with the severity of CSA-AKI regardless if renal function was restored at discharge, which was in accordance with the findings of previous studies [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recently AKI and CKD were found to be interconnected syndromes with similar risk factors (i.e. older age, pre‐existing renal function impairment, diabetes mellitus, hypertension) . A substantial group of AKI patients develop CKD and even proceed to end‐stage renal disease (ESRD) after severe AKI.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kim et al reported that persistent AKI (defined as incomplete reduction of serum creatinine at 7 days) after gastric surgery was associated with CKD progression 1 year later 12 . Similarly, the duration of AKI after cardiac surgery was also regarded as a strong independent risk factor for CKD development 13 . In addition, a recent retrospective study indicated that 29% of patients with elective cardiac surgery and cardiopulmonary bypass experienced AKI and notably, half of these AKI patient developed CKD 14 .…”
Section: The Aki-ckd Connectionmentioning
confidence: 99%